Assessment Of Quality of Life Among PLHIV Attending the FIART Clinic of Bankura Sammilani Medical College, West Bengal - Dey, Surya Prakash; Bhattacharya, Tridibes; Sarkar, Aditya Prasad (National Journal of Community Medicine, 2022)
Introduction: People Living with HIV (PLHIV) are facing increasing Physical, Social, Psychological challenges pertaining to the disease as life expectancy is gradually rising. This study was conducted to assess the quality of life (QOL) in respect of various domains among PLHIV and to find out its’ associated factors. Methods: An institute-based descriptive, cross-sectional study was conducted in FIART clinic of Bankura Sammilani Medical College & Hospital among 99 PLHIV selected by systematic random sampling technique from 1st July 2019 to 30th June 2020. Data were collected by interviewing PLHIV aged within 18-60 years using semi-structured questionnaire incorporating WHO Quality of Life for HIV (WHOQOL-HIV) - BREF version to assess the QOL of the study subjects in various domains. Results: 44% participants rated their QOL as good, while 79% satisfied with their health. QOL score was found highest in physical domain (median- 17.0, IQR- 4) and lowest in spiritual domain (median- 14.0, IQR- 2). Overall QOL was significantly higher in males, resident of rural area, individuals belonging to joint family and higher socio-economic class. Multiple linear regression revealed statistically significant relation of overall QOL with residence, type of family and socio-economic status. Conclusion: Psychological and spiritual well-being of PLHIVs are an area of concern and requires clinical attention.